Analisis Kesalahan Mahasiswa dalam Menyelesaikan Soal Negasi Pernyataan Majemuk pada Logika Matematika - Mutia Mutia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
This research aims to determine what kind of mistakes made PGMI students even semester of the academic year 2016/2017 in solving the problem of compound statement negation on mathematical logic and to know the alternative solution. The type of this research is descriptive research with qualitative approach. The research instrument used in this research is mathematical logic test and interview. The data analyzed is the result of student work on the worksheet that made a mistake. The results of this study indicate that students experience some errors that are marking errors, mistranslate logic symbols, concept errors, mistakes remembering the truth value in the statement truth table, and error concluded. After knowing the types of mistakes made by students in working on the question of negation of compound statements, then the alternative solution that can be given to this research problem is to use learning techniques that enable students to think well Like discussing, speaking and writing in front of the class to explain Directly so that students can retain their memories much longer, emphasizing the importance of much work on the matter by watching the right symbols or practicing remembering and writing symbols through the questions, giving repetitive exercise of different types of questions, and routine assignments To be memorized by truth values in mathematical logic.